Unemployment, Marginal Attachment, and Labor Force Participation in Canada and the United States - Jones, Stephen R. G.; Riddell, W. Craig (Journal of Labor Economics, 2019)
We analyze changes in unemployment, marginal labor force attachment, and participation in Canada and the United States using consistent measurement concepts. We show the importance for the comparative evolution of aggregate unemployment of changes in the fraction of those “wanting work”—the unemployed and marginally attached. We also study changes in the fraction of the nonemployed who are unemployed. Using micro data on labor market transition behavior at these margins, we find remarkably consistent results in the two countries, with the marginally attached displaying behavior lying between unemployment and nonattachment. The three nonemployment states are distinct in both countries.